What we inherit : a secret war and a family's search for answers - Rotondi, Jessica Pearce, 1985- (The Unnamed Press, 2020)
After years of being misled by the US government, Jessica Pearce Rotondi travels to Laos with the hope of finding answers for her family, but instead finds a country still reeling from a secret war.